2018
DOI: 10.32038/ltrq.2018.08.01
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gallery Walk Technique on Pre-intermediate EFL Learners’ Speaking Skill

Abstract: A "Gallery Walk" is an action that permits students to examine and show their last work around a room much like artists would show their artistic pieces in a "exhibit." It is a way that learners can share their group tasks or individual responses to a content in a stress-free way with the confirmation of getting some feedback from their learning network. This study investigated the impact of gallery walk technique on Iranian pre-intermediate EFL students' oral execution. Firstly, 60 homogeneous pre-intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 4 publications
1
31
0
2
Order By: Relevance
“…Each outline includes a specific question that relates to a key lesson topic. The method comes to an end with an oral presentation in which each group combines comments on a given topic (Cheng, 2006;Anwar, 2015;Namaziandost, Esfahani, Nasri, & Mirshekaran, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Each outline includes a specific question that relates to a key lesson topic. The method comes to an end with an oral presentation in which each group combines comments on a given topic (Cheng, 2006;Anwar, 2015;Namaziandost, Esfahani, Nasri, & Mirshekaran, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In various exciting and intuitive ways, the Gallery Run conjoins students to one another and the course subject (Ridwan, 2019). Namaziandost, Esfahani, Nasri, and Mirshekaran (2018) believed that speaking, listening, reading, and writing are the four major skills in English language training. For two reasons, many people believe that speaking another language is more complicated than the other three talents.…”
Section: Introductionmentioning
confidence: 99%
“…The assumption called encoding of variation points out that contents presented in spaced distribution are more quickly retrieved compared with massed resources, because every display in spacing distribution is treated as a new form and thereupon offers the learner additional clues. In reality, as stated by Anderson and Bower (1972) and Namaziandost et al (2018), this theory focuses on the function of the actual form and suggests that an entry included in a context is codified along with definition. Furthermore, the notion of deficient elaboration indicates that massed distribution cannot result in sufficient content production, as held by Challis (1993).…”
Section: Literature Reviewmentioning
confidence: 99%
“…She claimed that the use of debate improved students' speaking performance simultaneously with their creative thinking. Gallery Walk Technique, Experience-based learning strategies, and Comprehension check strategies increased students speaking ability [5,6,7]. Another type of strategy, Zohairy [8] found that pair work strategies illustrated the different perception between Saudi students and the teacher.…”
Section: Introductionmentioning
confidence: 99%